Long term results and complications of trabeculectomy augmented with low dose mitomycin C in patients at risk for filtration failure. Issue 6 (1st June 2001) - Casson, Robert; Rahman, Rubina; Salmon, John F
Abstract : AIM: To determine the results and complications up to 5 years after trabeculectomy with 0.02% mitomycin C (MMC) in glaucoma patients at risk for failure of filtration surgery. METHODS: A consecutive series of 21 eyes from 20 patients who underwent trabeculectomy with MMC 0.02%, with an exposure time of 2 minutes, was retrospectively analysed and the results were compared with previously published data. RESULTS: The mean preoperative intraocular pressure (IOP) was 28 mm Hg on an average of 2.8 glaucoma medications, and the mean postoperative IOP after 3 years was 14 mm Hg on an average of 0.4 medications. Three years after trabeculectomy, 17 of 21 (80.9%) eyes had an IOP of less than 21 mm Hg without medical treatment. Using Kaplan-Meier life table analysis the 5 year probability of an IOP less than 21 mm Hg without medication was 67% and with medication was 90%. Two patients required further glaucoma surgery during the first postoperative year, and another developed hypotonous maculopathy which was reversed after bleb revision. Seven patients developed visually significant cataract as a late consequence of the surgery. There were no bleb related infections. CONCLUSION: In the long term MMC 0.02% used for 2 minutes intraoperatively is an effective adjunctive treatment in glaucoma patients at risk for bleb failure and in this dose is associated with few complications.